Modeling individual variation in early literacy skills in kindergarten children with intellectual disabilities. (January 2018) - van Tilborg, Arjan; Segers, Eliane; van Balkom, Hans; Verhoeven, Ludo
Highlights: Early literacy skills in children with intellectual disabilities were investigated. Children with ID scored lower than NLA peers on linguistic and cognitive skills. Variation in word decoding was predicted by letter knowledge and nonverbal reasoning. Arrears in phonological awareness puts literacy learning in children with ID on hold. Abstract: In the present study, we investigated (i) to what extent the early literacy skills (phonological awareness, letter knowledge, and word decoding) along with cognitive (nonverbal reasoning, attention, phonological short-term memory, sequential memory, executive functioning) and linguistic (auditory discrimination, rapid naming, articulation, vocabulary) precursor measures of 53 six-year old children with intellectual disabilities (ID) differ from a group of 74 peers with normal language acquisition (NLA) and (ii) whether the individual variation of early literacy skills in the two groups to the same extent can be explained from the precursor measures. Results showed that children with ID scored below the NLA group on all literacy and precursor measures. Structural equation modeling evidenced that in the children with NLA early literacy was directly predicted by phonological awareness, PSTM and vocabulary, with nonverbal reasoning and auditory discrimination also predicting phonological awareness. In children with ID however, the variation in word decoding was predicted by letter knowledge and nonverbal reasoning, whereas letter knowledge was predicted by rapid naming, which on its turn was predicted by attentional skills. It can be concluded phonological awareness plays a differential role in the early literacy skills of children with and without ID. As a consequence, the arrears in phonological awareness in children with ID might put them on hold in gaining proper access to literacy acquisition. What this paper adds: This paper adds to the theoretical knowledge base on literacy acquisition in a special population, namely children with intellectual disabilities (ID). It addresses factors that influence early literacy learning, which have not been investigated thoroughly in this special and specific group. Furthermore, the children are not tested solely on literacy, but also on cognitive measures that may influence literacy acquisition. Whereas most research in ID focuses on groups with specific syndromes/etiologies, this paper takes a varied group of children with ID into account. The paper also adds to educational insights, since the findings imply that children with ID are able to use phonological pathways in learning to read. Educators could teach these children phonics-based literacy skills tailored to their individual learning needs.